(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article provides a scientific and theoretical analysis of the process of changing family roles in modern society. As a result of socio-economic development, globalization, increased education levels, and the widespread spread of ideas about gender equality, the traditional model of family roles is undergoing significant transformation. The article highlights the main factors of changing roles between spouses, parents, and children, as well as their impact on family relationship.